Child-friendly e-learning for artificial intelligence education in Indonesia: conceptual design - Purbohadi, Dwijoko; Santoso, Joko (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
Due to the widespread use of smartphones, most children in Indonesia are now engaged in playing video games. To make these games more exciting and challenging, video game manufacturers often incorporate artificial intelligence (AI). While various studies have highlighted the benefits of playing video games for children, this research has revealed some significant negative impacts that need to be addressed, as they can affect children's prospects. One of the major detrimental effects is the growing negative perception towards robots and AI, with concerns that they will replace human jobs. To counteract these negative impacts, educational institutions in Indonesia need to proactively plan and prepare for the consequences of gaming through formal learning. Given Indonesia's vast territory, consisting of islands, and its large population, it is crucial to implement appropriate learning technology. This article presents the architectural design of a child-friendly e-learning system that focuses on teaching children about AI. The design considers the available technology in Indonesia, based on our experience. The child-friendly e-learning model for AI education is expected to cultivate an interest in learning about technology, thus diverting children's attention from video game addiction.